Discrepancies between patients' and pharmacists' perceptions of the role of community pharmacists as advisors on the use of pharmaceuticals in Japan: A comparison prior to and following revision of the Pharmacists' Act. (March 2019) - Oshima, Shinji; Yamagishi, Mari; Okita, Mitsuyoshi; Akimoto, Hayato; Negishi, Akio; Horii, Norimitsu; Mutoh, Mizue; Sannomaru, Yasuko; Numajiri, Sachihiko; Inoue, Naoko; Ohshima, Shigeru; Wada, Masahiro; et al.
Objectives: In 2014, immediately prior to the revision of Article 25-2 of the Pharmacists' Act, we conducted a survey on pharmacists' and patients' perceptions of pharmacists' roles. A role discrepancy between the two was identified. The objective was to examine changes in role perceptions and awareness of pharmacists as medication specialists following revision to the Pharmacists' Act. Methods: The survey was conducted using an Internet-based questionnaire. A total of 469 patients and 354 pharmacists responded to 12 questions about the perceived roles of pharmacists. Results: Analysis revealed that the only evaluation that changed as a result of revisions was pharmacists' role as "family or regular pharmacist, " with scores dropping by about half. As in 2014, the high rating rate for pharmacists surpassed the high rating of patients for all other items. The greatest discrepancy in role perception was observed for the same three items ("Understanding the effects of the drugs the patients are taking, " "Understanding the health changes caused by the drugs dispensed to the patients, " and "Consciously protecting patients from the adverse effects of drugs") as 2014. Conclusion: A major role discrepancy continues to exist between patients and pharmacists, and it is necessary for pharmacists to take on a more advanced role in patient care. Results suggest that pharmacists must monitor changes in patients' lifestyles and provide clear explanations for patients to rate them highly as medication specialists.